2009
DOI: 10.1007/s00531-009-0423-7
|View full text |Cite
|
Sign up to set email alerts
|

Magmatic erosion of the solidification front during reintrusion: the eastern margin of the Tuolumne batholith, Sierra Nevada, California

Abstract: The Tuolumne batholith, Sierra Nevada, California, consists of several nested granitoid units and is an example of upper-crustal normally zoned intrusions. The two outermost units of the batholith are separated by a wide gradational contact in what is interpreted to represent a large magma chamber. In the Potter Point area near the eastern margin of the batholith, the gradational contact is cross-cut by a network of interconnected mafic-felsic sheets, which grade into zones of magmatic erosion by stoping where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…instabilities can take different forms depending on the location of the layer and crystal growth in the chamber (e.g., Jaupart and Tait, 1995;Bergantz, 2000). For example, along the horizontal roof of a chamber, magma convection can produce chemical and physical instabilities that cause crystal-rich batches to descend, or "drip" , from the roof (e.g., Bergantz and Ni, 1999;Rocher et al, 2018), while at a vertical or sloping margin, convection would generate a sidewall current (e.g., Jaupart and Tait, 1995;Žák and Paterson, 2010;Paterson et al, 2016Paterson et al, , 2019. Marsh (1996Marsh ( , 2006Marsh ( , 2013Marsh ( , 2015 examined the growth of solidification fronts in chambers where the cooling is faster at the roof than at deeper levels along walls.…”
Section: Research Papermentioning
confidence: 99%
See 1 more Smart Citation
“…instabilities can take different forms depending on the location of the layer and crystal growth in the chamber (e.g., Jaupart and Tait, 1995;Bergantz, 2000). For example, along the horizontal roof of a chamber, magma convection can produce chemical and physical instabilities that cause crystal-rich batches to descend, or "drip" , from the roof (e.g., Bergantz and Ni, 1999;Rocher et al, 2018), while at a vertical or sloping margin, convection would generate a sidewall current (e.g., Jaupart and Tait, 1995;Žák and Paterson, 2010;Paterson et al, 2016Paterson et al, , 2019. Marsh (1996Marsh ( , 2006Marsh ( , 2013Marsh ( , 2015 examined the growth of solidification fronts in chambers where the cooling is faster at the roof than at deeper levels along walls.…”
Section: Research Papermentioning
confidence: 99%
“…Marsh (1996Marsh ( , 2006Marsh ( , 2013Marsh ( , 2015 examined the growth of solidification fronts in chambers where the cooling is faster at the roof than at deeper levels along walls. He suggested that these fronts may detach from the roof, generating a crystal-rich magma avalanche toward hotter and deeper levels of the chamber (e.g., Žák and Paterson, 2010). Davis et al (2007) used the concept of transient particle pressure in magma slurries to argue that magmas affected by earthquake activity could partially fluidize crystal mushes in seconds, resulting in an instantaneous decrease in pressure in the melt phase, in situ bubble formation, and thus large-scale destabilization of the mush, similar to the deformation of wet sediments during seismic loading (e.g., Sumita and Manga, 2008).…”
Section: Research Papermentioning
confidence: 99%
“…A more geographically extensive examination of the dikes and larger, internally layered sheets in the Potter Point area indicates that they form two systematic sets based upon their orientation and crosscutting relationships (see Žák and Paterson, 2010): (1) an older, ~290°-310° striking, steeply dipping, predominantly dioritic set, and (2) a younger, ~30°, steeply dipping, predominantly felsic set. However, several cases of reverse or more complex crosscutting relationships were observed.…”
Section: Figure 3 (Continued) Field Photos Of Turner Lake Granite Blmentioning
confidence: 99%
“…1). In this paper we focus on four areas: (1) Žák and Paterson, 2010); (3) in and around the metasedimentary May Lake pendant near the western margin of the batholith (Figs. 6 and 7); and (4) in the Jackass Lakes pluton, where we focus on block formation near pendants and continued disaggregation of individual stoped blocks once they were engulfed by magma in the magma chamber (Figs.…”
Section: Plutons Examinedmentioning
confidence: 99%
“…Chambers capable of generating large-volume eruptions are widely viewed as a transient high-melt zone or zones within much larger, vertically integrated and variably crystallized "mush columns" (e.g., Marsh, 2000Marsh, , 2006Vazquez and Reid, 2002;Glazner et al, 2004;de Silva and Gosnold, 2007;Bachmann et al, 2007;Bachmann and Bergantz, 2008a;Annen, 2011). However important questions remain regarding the time evolution, and the nature, scales, and magnitudes of magmatic heterogeneities and related petrogenetic processes operating within these columns (e.g., Bachmann and Bergantz, 2004;Cathey and Nash, 2004;Smith et al, 2005;Shane et al, 2007Shane et al, , 2008, and regarding the way in which material may be recycled within these systems (Vazquez and Reid, 2002;Miller et al, 2007;Bindeman et al, 2008;Zak and Paterson, 2010).…”
Section: Introductionmentioning
confidence: 99%